PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERCATAT DI BEI TAHUN 2012-2014) - Giovanni Anggarda Zakaria; Handoyo Djoko W (Universitas Diponegoro, 2017)
Competition among businesses has been increasing at the era of globalization. Growingconsumer demand encourages manufacturers to improve themselves in order to survive incompetition. One effort that can be done is to improve managerial performance and innovation.Therefore, companies need to consider not only the tangible assets but also intangible assetstowards knowledge-based businesses.This study aims to determine whether there is influence between Intellectual Capital(Human Capital, Structural Capital and Capital Employed) on the performance of the consumergoods industry companies listed on the Indonesia Stock Exchange in the year 2012-2014. Type ofthis study use explanative type. Technique sampling from this study is saturation sampling. Thepopulation used a total of 35 consumer goods industry companies listed on the Indonesia StockExchange in 2012-2014. This study use SPSS for Mac version 21.Results from the study showed that there is no significant relationship between HumanCapital and Corporate Performance, as well as the Structural Capital is no significant effect onthe Company's Performance. However, Capital Employed has a significant impact on theCompany's Performance. Based on these results it can be said that the performance can beaffected by the Company's Capital Employed which means the relationship between the companyand external parties can better improve the company's performance. The recommendation iscompanies should pay attention to manage intangible assets, especially Capital Employed becauseit can affect the performance of companies.